Employment of fiber laser technology to weld austenitic stainless steel 304 l with aluminum alloy 5083 using pre-placed activating flux - Ezazi, M.A.; Yusof, Farazila; Sarhan, Ahmed Aly Diaa Mohammed; Abd Shukor, Mohd Hamdi; Fadzil, M. (Elsevier, 2015)
The overlapping welding was carried out in keyhole mode between austenitic stainless steel 304 l and aluminum alloy 5083 using a low power fiber laser in continuous irradiation. The significant content of magnesium as the alloying element with low boiling point and high vapor pressure inside the AA 5083 matrix can induce the spatter formation and depression on surface of the weld beads upon laser beam absorption and temperature growth which can deteriorate the mechanical properties and appearance of the joints. To reduce these defects, a variety of single and multi-components activating fluxes including oxide-based TiO2 and halide-based CaF2 flux powders were pre-placed on the surface of welding material prior to laser welding. The EDX and XRD analyses in addition to microhardness and shear tests were carried out to characterize the joints. The obtained results showed that, the oxide and halide activating fluxes can significantly improve the joints' strength up to 1.48 and 1.85 times in average respectively compared with autogenous joint. It was deduced that the simultaneous effect of significant decrease in joints' surface depression leading to welds' geometry improvement in addition to less formation of interfacial Fe-Al intermetallics, were the major causes for considerable strength improvements. (C) 2015 Elsevier Ltd. All rights reserved.